2012
DOI: 10.1001/archdermatol.2011.3227
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Distribution of Malignant Melanoma on the Non-Hispanic Black Patient, 1998-2007

Abstract: Objectives: To provide a population-based description of the anatomic distribution of melanoma among non-Hispanic black patients and to explore how characteristics of this distribution relate to the etiologies previously reported for both white and black patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
(53 reference statements)
4
11
0
1
Order By: Relevance
“…Other studies in Black populations showed similar reports with the lower limb being the most common anatomical site (4,7,8,11,18) and the foot being the most common lower limb site and the commonest site overall (4,7,11). However, the second commonest anatomical location reported in other Black populations was either the trunk (8,11,18) or upper limb (4,7,8) unlike in our study. In Caucasian populations, the most common anatomical location for males is the trunk and the lower limb is the commonest in females (8,22).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Other studies in Black populations showed similar reports with the lower limb being the most common anatomical site (4,7,8,11,18) and the foot being the most common lower limb site and the commonest site overall (4,7,11). However, the second commonest anatomical location reported in other Black populations was either the trunk (8,11,18) or upper limb (4,7,8) unlike in our study. In Caucasian populations, the most common anatomical location for males is the trunk and the lower limb is the commonest in females (8,22).…”
Section: Discussionsupporting
confidence: 88%
“…In the USA, on the one hand, an increase has been documented in recent years (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001) In this study, CMM was most commonly seen in the seventh decade (median ages: males 61 years and females 63 years). A similar age distribution was observed in other Black populations (7,18). Butler, however, reported a lower median age (6 th decade) in both males and females in his study (11) and Lodder et al reported a much wider age distribution, ranging from the 6 th to 7 th decades, in Black South Africans (4).…”
Section: Discussionsupporting
confidence: 79%
“…Malignant melanoma (MM) is an aggressive form of skin cancer, and over the past 30 years, has had one of the most rapidly increasing incidences of all cancer types . MM is a particularly resilient cancer, is responsible for 75% of skin cancer‐related deaths worldwide, and is the most common fatal malignancy in young adults .…”
Section: Introductionmentioning
confidence: 99%
“…Le siège électif du mélanome au niveau des pieds chez l´Africain a fait suggérer dans le passé le rôle des microtraumatismes répétés dus à la marche pieds nus [17]. Mais ce rôle est exagéré, car on observe la même fréquence de localisation des extrémités chez les Noirs Américains [14, 15]. De façon générale les variétés histopathologiques les plus observées chez le noir africain sont le type acrallentigineux et le type nodulaire [7, 10, 12, 18], contrairement aux résultats de Garbe [19] qui notait que le mélanome superficiel extensif (SSM) était le type histopathologique le plus fréquent chez le caucasien.…”
Section: Discussionunclassified